Transcobalamin 2 orchestrates monocyte proliferation and TLR4-driven inflammation in systemic lupus erythematosus via folate one-carbon metabolism - Liu, Baoyi; Li, Ang; Liu, Yi; Zhou, Xinzhu; Xu, Jingkai; Zuo, Xianbo; Xue, Ke; Cui, Yong (Frontiers in Immunology, 2024)
Background: SLE is a complex autoimmune disease with deleterious effects on various organs. Accumulating evidence has shown abnormal vitamin B12 and one-carbon flux contribute to immune dysfunction. Transcobalamin II (TCN2) belongs to the vitamin B12-binding protein family responsible for the cellular uptake of vitamin B12. The role of TCN2 in SLE is still unclear.Methods: We collected clinical information and blood from 51 patients with SLE and 28 healthy controls. RNA sequencing analysis, qPCR, and western blot confirmed the alteration of TCN2 in disease monocytes. The correlation between TCN2 expression and clinical features and serological abnormalities was analyzed. TCN2 heterozygous knockout THP1 cells were used to explore the effects of TCN2 dysfunction on monocytes. CCK-8 assay and EdU staining were used to detect cell proliferation. ELISA was conducted to assess vitamin B12, glutathione, and cytokines changes. UHPLC-MRM-MS/MS was used to detect changes in the intermediates of the one-carbon cycle. Flow cytometry is used to detect cell cycle, ROS, mitoROS, and CD14 changes.Results: Elevated TCN2 in monocytes was correlated positively with disease progression and specific tissue injuries. Using CD14+ monocytes and TCN2 genetically modified THP1 cell lines, we found that the TCN2 was induced by LPS in serum from SLE patients. TCN2 heterozygous knockout inhibited cellular vitamin B12 uptake and one-carbon metabolism, leading to cell proliferation arrest and decreased Toll-like receptor 4 (TLR4)-mediated CCL2 release. Methionine cycle metabolites, sadenosylmethionine and homocysteine, rescued these effects, whereas folate treatment proved to be ineffective. Folate deficiency also failed to replicate the impact of TCN2 downregulation on THP1 inflammatory response.Our study elucidated the unique involvement of TCN2-driven one-carbon flux on SLEassociated monocyte behavior. Increased TCN2 may promote disease progression and tissue damage by enhancing one-carbon flux, fostering monocyte proliferation, and exacerbating TLR4 mediated inflammatory responses. The inhibition of TCN2 may be a promising therapeutic approach to ameliorate SLE.